Structural and electronic modifications of pyridones and pyrones via regioselective bromination and trifluoromethylation. Issue 31 (3rd August 2017) - Seo, Junhyeok; Sotman, Timothy E.; Sullivan, Eileen R.; Ellis, Bryan D.; Phung, Truc; Rose, Michael J.
Abstract: We report regioselective functionalization of pyridones and pyrones via electrophilic bromination (Br2 ) or radical trifluoromethylation (NaSO2 CF3 / t BuOOH) at the 3-position. Counter-intuitively, the 3-position EW groups decreased the carbonyl stretching energy by 6–23 cm −1 ; however, 3, 5-dibromination increased the CO frequency by 10–22 cm −1 compared to the 3-Br pyridones. X-ray crystallography revealed pyridone tautomers with contracted CO bond metrics. p K a values and 1 H NMR shifts for the series 3-H→Br→CF3 revealed the expected trend of increasing acidity ( p Ka  = 8.85 → 8.33→6.78, MeOH) and increasing chemical shifts (10.97 → 11.42→11.71 DMSO- d 6 ). We conclude that the paradoxical decrease in CO stretching frequencies by the 3-positoin EW groups is explained by an 'assistive' electron-withdrawing effect, whereby the 3-position EW group assists the electronegative oxygen atom in recruiting more electron density, and – as a result – attaining more oxyanion character (decreased the CO bond strength). Graphical abstract: